Mari's novel T shaped incision in frenotomy technique with bilateral pedicle flap- an aesthetic approach - K. Rudhra; Ranjith Mari; Anitha Balaji; Mohan Valiathan (Journal of Oral Biology and Craniofacial Research)
Background: Aberrant frenum attachments often lead to mucogingival deformities, culminating in both functional impairments and aesthetic concerns. Traditional frenectomy procedures are associated with extensive incisions and resultant wound defects. To address these challenges, a novel T-shaped incision technique has been developed. This method enhances accessibility for removing vestibular and frenal attachments while creating a tripod layer of flaps, thereby promoting primary closure and improved blood supply for healing by primary intention. Case management: This innovative technique is particularly suited for managing frenum variations such as bifid frenum, persistent tectolabial frenum, double frenum, and wider frenum. The procedure involves crafting two horizontal and two converging parallel incisions that form a “T'' shape, facilitating effective fiber detachment. Bilateral pedicle flaps are then employed for primary closure, which concurrently enlarges the zone of attached gingiva. Conclusion: The T-shaped incision approach presents an advanced method for treating abnormal frenum attachments, ensuring efficient fiber separation and fostering healing by primary intention.